2016
DOI: 10.1111/jocn.13255
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of semi‐rigid ankle brace to facilitate return to work following first‐time acute ankle sprains

Abstract: The findings of this economic evaluation provide justification for the use of semi-rigid ankle brace by Musculoskeletal Physiotherapists and Nurses to facilitate return to work in individuals with first-time ankle sprains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…For protection, ankle support may be indicated to facilitate return to work. A semirigid brace is suggested to be the most cost-effective option compared with taping208 (level 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For protection, ankle support may be indicated to facilitate return to work. A semirigid brace is suggested to be the most cost-effective option compared with taping208 (level 3).…”
Section: Resultsmentioning
confidence: 99%
“…Preventive efforts against first-time and recurrent ankle sprains have shown high cost benefits208 (level 3). Both neuromuscular training and ankle braces have been proven beneficial as a preventive investment due to lower societal costs, mainly achieved through reduced indirect costs209 (level 2).…”
Section: Resultsmentioning
confidence: 99%
“…Dobson DaVanzo & Associates Report 2013 and the Queensland Artificial Limb Scheme Report 2018 are also peer-review published) [14, 25–27]. This testing was conducted through hand-searching the reference list of known peer-reviewed studies [1217, 2830] and an assessment of known grey literature [25, 27, 31, 32] and confirmed the appropriateness of this search strategy limitation.…”
Section: Methodsmentioning
confidence: 88%
“…Niu et al investigated the effects of different ankle braces on lower limb biomechanics during HSPL and revealed that rigid ankle brace usage could enhance muscle activity [17]. Some scholars acknowledged that elastic deformation of the support structure on both sides of the ankle brace provided an eversion moment to overcome inversion and reduced the work [31]. Based on Janssen et al's [7] Constructs of Subjective Factors of Brace Use, the questionnaires were designed using the Likert 5 point scale for each evaluation index, including ease of use, quality, comfort, stability, hindrance, and satisfaction.…”
Section: Discussionmentioning
confidence: 99%